Marketing and entrepreneurship : the case of firms in Iceland - Kristófer Kristófersson 1990- (2017)
The intention of this study is to gain an understanding of how marketing is practiced in the entrepreneurial environment and to identify and determine how the seven major dimensions of the entrepreneurial marketing (EM) theory presents within the marketing practices of Icelandic entrepreneurial firms. The topic of entrepreneurial marketing is new in the literature and the Icelandic business environment, which constitutes many young firms after the banking crisis of 2008, making this an ideal topic for this field of study. The companies in this research are less than 15 years old, have fewer than around 100 employees and have all launched a product recently or are in the final stages of product development. Based on the seven dimensions of EM, a unique list of questions was composed for qualitative research, which involved in-depth semi-structured interviews with the firm’s marketers or executive directors. The interviews were transcribed and then analyzed through descriptive analysis. The results from the explorative research show that the marketing methods of the companies studied align with the current theory of entrepreneurial marketing, which can be briefly described as a pro-active identification of openings in the market for obtaining and retaining customers through innovative methods to managing risks, resources and creating value. Keywords: Entrepreneurial Marketing, EM, Entrepreneurs, Entrepreneurship, Iceland, Innovation, Marketing Environment.